Effect of CO2 Huff and Puff Rounds on Crude Oil Properties - Qionglin Shi; Sha Gong; Xiaoping Qin (Journal of Chemistry)
In view of the deterioration of oil well liquid supply capacity and oil increase effect after multiple rounds of carbon dioxide (CO2) huff and puff, according to the actual conditions of the Ng12 reservoir in the XA oilfield, an indoor physical simulation experimental model was established. The experimental parameters were determined, five rounds of CO2 huff and puff experiments were carried out, and the crude oil produced in the water flooding stage and different rounds of CO2 huff and puff were collected. The effects of CO2 huff and puff rounds on crude oil viscosity, density, composition, paraffin content, and gum asphaltene content were studied. The results show that with the increase in CO2 huff and puff rounds, the viscosity and density of produced crude oil decrease. The content of light component (C2∼C6) and intermediate component (C7∼C10) increased, while the content of heavy component (C11+) decreased. CO2 has the strongest extraction effect on light components and the weakest extraction effect on heavy components. At the same time, the content of paraffin and gum asphaltene in the produced crude oil is reduced. For oil wells with multiple rounds of CO2 huff and puff, colloidal asphaltene precipitation inhibitor and scavenger should be considered to reduce the impact of colloidal asphaltene on formation permeability and liquid supply capacity.